Islamic Value-Based Entrepreneurial Organizational Planning: An Innovative Strategy for Building Sustainable Enterprises - Dina Sutiana; Saca Suhendi; Hasbiyallah (LECTURES: Journal of Islamic and Education Studies, 2025)
This study explores entrepreneurial organizational planning as a strategic approach to building effective, competitive, and value-driven ventures. Using a qualitative descriptive method through literature review, the article examines four key aspects of organizational planning: fundamental concepts, planning tools, planning processes, and strategic approaches. In a rapidly changing economic and technological landscape, entrepreneurs are required to design organizations that are adaptive yet purposeful. This study emphasizes the importance of integrating Islamic values into organizational planning to ensure that the process is not only operationally efficient but also ethically sound and socially beneficial. Values such as honesty, trustworthiness, social responsibility, and public benefit (maslahah) serve as the spiritual foundation that guides planning towards a balance between worldly success and eternal values. The findings reveal that combining modern planning tools (such as the Business Model Canvas and SWOT) with adaptive approaches (such as effectuation, lean startup, and design thinking) provides a robust framework for contextually relevant and impactful business planning. Therefore, this article offers an integrative, value-based planning model rooted in Islamic principles, aimed at fostering sustainable and impactful entrepreneurial organizations.